THE GENESIS OF ISLAMIC SCIENCE: THE CONTRIBUTION OF CLASSICAL INDIAN SCIENCE REVISITED - Bakar, Osman (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2023)
The main purpose of this article is to highlight the historical fact that classical Indian civilisation played a significant role in the early civilisational growth of Islam during the three centuries under study, particularly in the field of philosophical-scientific knowledge. The Indian role is now acknowledged to be far more extensive than what many people thought and realised. Quite clearly, the Indian contribution helped pave the way for Islam’s grand knowledge synthesis or its golden age in the tenth and eleventh centuries. Unfortunately, in the Western-centric narrative of the history of science, the role of classical Indian science in the early development of Islamic civilisation was downplayed, with disproportionate prominence given to the role of Greek science. As a result, many Easterners today – Hindus and Muslims included – are unaware of the real extent of the classical Indian role in question. A significant facet of this early civilisational growth of Islam was knowledge transfer from the advanced cultures of the time, of which India was a good example. Rather interestingly, this knowledge transfer appeared to be widely known to the Muslims of the time. According to Joseph Mazur, “by the tenth century, there were numerous Arabic texts on the Indian numerals.” Another notable facet is knowledge organisation, which Muslims consciously pursued in the light of the distinct worldview of the new religion and civilisation. I will now explain what I mean exactly by the term knowledge transfer and the term knowledge organisation that I am using in this article. I will also explain the classical Indian connection to the knowledge activities that were going on in the young Islamic civilisation.